Sizzling sixteen [compact disc, unabridged] - Evanovich, Janet (Evanovich, Janet. Stephanie Plum novel., 2010)
When bounty hunter Stephanie Plum inherits a lucky bottle from an uncle, she discovers that the bottle brings both good and bad luck. Her cousin and employer, Vinnie, has racked up a huge gambling debt with the Mob and disappeared. Now Stephanie is responsible for paying off the debt and making sure Vinnie stays out of harm's way.